Educating Human Being. On Manuel Granell’s Humanism - Scotton, Paolo (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
A common trait that ties Spanish philosophy and Latin American thought is represented by the strong connection between theoretical and practical knowledge. Indeed, philosophy is conceived both as a practical activity connected to the life experience of each person, and as means for reforming society. By taking into consideration the development of the Spanish liberal thought, in particular during the first half of the 20th century, this article analyses the original contribution to this philosophical perspective offered by Manuel Granell. This critical discussion aims to point out the relevance of Granell’s conception of ethology as a theoretical premise for the development of a renewed concept of humanistic philosophy and education, both in the Latin America context and in the global scenario.
Keywords: Latin American philosophy; Liberalism; Humanistic education; Manuel Granell.